Association of Lower Fractional Flow Reserve Values With Higher Risk of Adverse Cardiac Events for Lesions Deferred Revascularization Among Patients With Acute Coronary Syndrome. Issue 8 (19th August 2015) - Masrani Mehta, Shriti; Depta, Jeremiah P.; Novak, Eric; Patel, Jayendrakumar S.; Patel, Yogesh; Raymer, David; Facey, Gabrielle; Zajarias, Alan; Lasala, John M.; Singh, Jasvindar; Bach, Richard G.; Kurz, Howard I.
Abstract : Background: The safety of deferring revascularization based on fractional flow reserve (FFR) during acute coronary syndrome (ACS) is unclear. We evaluated the association of FFR and adverse cardiac events among patients with coronary lesions deferred revascularization based on FFR in the setting of ACS versus non‐ACS. Methods and Results: The study population (674 patients; 816 lesions) was divided into ACS (n=334) and non‐ACS (n=340) groups based on the diagnosis when revascularization was deferred based on FFR values >0.80 between October 2002 and July 2010. The association and interaction between FFR and clinical outcomes was evaluated using Cox proportional hazards models within each group (mean follow‐up of 4.5±2.1 years). Subsequent revascularization of a deferred lesion was classified as a deferred lesion intervention (DLI), whereas the composite of DLI or myocardial infarction (MI) attributed to a deferred lesion was designated as deferred lesion failure (DLF). In the non‐ACS group, lower FFR values were not associated with any increase in adverse cardiac events. In the ACS group, every 0.01 decrease in FFR was associated with a significantly higher rate of cardiovascular death, MI, or DLI (hazard ratio [HR], 1.08; 95% confidence interval [CI], 1.03 to 1.12), MI or DLI (HR, 1.09; 95% CI: 1.04 to 1.14), DLF (HR, 1.12; 95% CI, 1.06 to 1.18), MI (HR, 1.07; 95% CI, 1.00 to 1.14), and DLI (HR, 1.12; 95% CI, 1.06 to 1.18). Conclusion: Lower FFR values among ACS patients with coronary lesions deferred revascularization based on FFR are associated with a significantly higher rate of adverse cardiac events. This association was not observed in non‐ACS patients.